KURIKULUM PENDIDIKAN ISLAM DALAM PERSPEKTIF TOKOH PENDIDIKAN ISLAM - Fauzan Fauzan (SCAD Independent, 2014)
Many scholars who have authority over a field of science is strong evidence of our scholars do not recognize the concept of science dichotomy. in the view of Islam, to some extent, controlled all mandatory. Just call it a distinguished, if studied theology (the basics) was fard 'ayn. That is mandatory for every Muslim man to learn. While studying general sciences is fard kifayah. The division of science becomes fard 'ayn and fard kifayah or Naqli science and science' aqli not need to be understood in a dichotomous or face to face, because he is just sharing knowledge hierarchy based on the level of taklif, needs, priorities and truth. It talks about the views of leaders of Islamic education in the mapping sciences/ teaching materials, which in terms of education today known as the